Clinical feasibility of pre-operative neurodevelopmental assessment of infants undergoing open heart surgery - Campbell, M.; Rabbidge, B.; Ziviani, J.; Sakzewski, Leanne (Wiley-Blackwell Publishing Ltd., 2017)
© 2017 Paediatrics and Child Health Division (The Royal Australasian College of Physicians) Aim: Assessing the neurodevelopmental status of infants with congenital heart disease before surgery provides a means of identifying those at heightened risk of developmental delay. This study aimed to investigate factors impacting clinical feasibility of pre-operative neurodevelopmental assessment of infants undergoing early open heart surgery. Methods: Infants who underwent open heart surgery prior to 4 months of age participated in this cross-sectional study. The Test of Infant Motor Performance and Prechtl's Assessment of General Movements were undertaken on infants pre-operatively. When assessments could not be undertaken, reasons were ascribed to either infant or environmental circumstances. Demographic data and Aristotle scores were compared between groups of infants who did or did not undergo assessment. Binary logistic regression was used to explore associations. Results: A total of 60 infants participated in the study. Median gestational age was 38.78 weeks (interquartile range: 36.93–39.72). Of these infants, 37 (62%) were unable to undergo pre-operative assessment. Twenty-four (40%) could not complete assessment due to infant-related factors and 13 (22%) due to environmental-related factors. For every point increase in the Aristotle Patient-Adjusted Complexity score, the infants likelihood of being unable to undergo assessment increased by 35% (odds ratio: 0.35; 95% confidence interval: 1.03–1.77, P = 0.03). Conclusion: Over half of the infants undergoing open heart surgery were unable to complete pre-operative neurodevelopmental assessment. The primary reason for this was infant-related medical instability. Findings suggest further research is warranted to investigate whether the Aristotle Patient-Adjusted Complexity score might serve as an indicator to inform developmental surveillance with this medically fragile cohort.